Mengukur Kinerja Organisasi Dari Perspektif Employee Green Behavior - Irwan Yantu; Rezkiawan Tantawi; Ikhlasul Amalriadna Abubakar; Given Ray Timothi Yahya (Universitas Batanghari, 2023)
This study utilizes descriptive quantitative methods with the objective of measuring the performance of higher education institutions from the perspective of employee green behavior. The measurement instrument employed was a questionnaire consisting of eight questions, which was distributed to 300 respondents. The responses provided by the participants were converted into an index using a scale range of 1-3. The resulting index serves as the foundation for researchers to determine whether the organizational performance falls within the 'high' category or ‘low’. The respondents consisted of lecturers from six universities in the Province of Gorontalo. The number of respondents was determined through purposive sampling, and the selection process was conducted randomly. The study's findings indicate that employee engagement in environmentally friendly behavior has a positive impact on organizational performance. However, the study also reveals that university performance does not exhibit a positive trend when evaluated from the perspective of employee green behavior.